2020
DOI: 10.1136/bmjsrh-2018-200271
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of artificial intelligence (AI)-enabled chatbots, video consultations and live webchats as online platforms for sexual health advice

Abstract: ObjectivesSexual and reproductive health (SRH) services are undergoing a digital transformation. This study explored the acceptability of three digital services, (i) video consultations via Skype, (ii) live webchats with a health advisor and (iii) artificial intelligence (AI)-enabled chatbots, as potential platforms for SRH advice.MethodsA pencil-and-paper 33-item survey was distributed in three clinics in Hampshire, UK for patients attending SRH services. Logistic regressions were performed to identify the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 17 publications
(17 reference statements)
1
48
0
Order By: Relevance
“…They are able to provide useful information when healthcare providers are unavailable (e.g., after clinic hours) or the patient prefers not to discuss with a healthcare provider (e.g., too anxious or embarrassed). However, a recent study showed that less than half of the surveyed population, 257 sexual and reproductive clinic users in UK, found chatbots favorable possibly due to concerns about perceived lack of confidentiality, empathy, and security [43]. Regulation of chatbots and mobile applications is therefore essential.…”
Section: The Future Of Ehealth Tools In Delivering Laboratory Resultsmentioning
confidence: 99%
“…They are able to provide useful information when healthcare providers are unavailable (e.g., after clinic hours) or the patient prefers not to discuss with a healthcare provider (e.g., too anxious or embarrassed). However, a recent study showed that less than half of the surveyed population, 257 sexual and reproductive clinic users in UK, found chatbots favorable possibly due to concerns about perceived lack of confidentiality, empathy, and security [43]. Regulation of chatbots and mobile applications is therefore essential.…”
Section: The Future Of Ehealth Tools In Delivering Laboratory Resultsmentioning
confidence: 99%
“…AI has emerged with particular strength in the medical domain over the recent years, where there are prolific proofs of its advances, strengths and opportunities in prognosis, diagnosis, healthcare or preventive medicine [49][50][51][52][53]. Besides, AI can be applied in the public health landscape by leveraging social network and Web 2.0 media data, which in turn can be exploited to control drug abuse [54,55], toxic substance consumption [56], sexual and reproductive health [57], as well as healthy life habits [58][59][60]. These data, along with those provided by wearable devices, constitute another valuable information source for developing personalized recommender systems to promote healthy habits and support better individual decision-making in terms of healthy choices [60][61][62].…”
Section: Analysis For the Economic Dimension: Lifementioning
confidence: 99%
“…Jaroszewski et al (2019) reported that, during clinical trials of their MLbased DDSS for mental illness prevention, only 28% of participants answered "very likely" to the question presented by the DDSS: "Be honest, how likely are you to try the resources I just shared?". Nadarzynski et al (2020) studied the acceptability of information systems dedicated to sexual health prevention. The authors reported that, for the first contact, 70% of patients preferred face-to-face consultations.…”
Section: A Questionable Acceptabilitymentioning
confidence: 99%